Upravljanje znanja, delavski sindikati in skupna posvetovalna telesa v primerjalni analizi - Štebe, Janez (Teorija in praksa, 2006)
The present study focuses on the platforms of knowledge in organisations. The process of knowledge creation occurs as a social process, which can be tampered with and therefore managed. We are interested in the organisational infrastructure that enables the dissemination of knowledge, HRM strategies and policies that accelerate knowledge management processes and the managing of the knowledge creation processes themselves. The role of trade unions and joint consultative committees come under particular scrutiny. The results of the analysis show how knowledge management strategies are shaped in organisations, and how these strategies are present in different institutional contexts. Six countries were included in the research - UK, Germany, Sweden, Netherlands, Czech Republic, Slovenia - and 2,357 organisations. The analysis showed that different strategies of knowledge management exist and that we can speak of Anglo-Saxon, Scandinavian, and Rhineland models of knowledge management, where strategies of knowledge management differ with regard to their elements and levels of success.
Keywords: Knowledge management; Upravljanje znanja; Organizacije; Organizations; Sindikati; Trade unions; Human resource management; Upravljanje s človeškimi viri; podjetje; corporation; management; upravljanje; človeški viri; strategija